(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This present paper makes that how Ranjit Singh make Maharaja and conquest the most of the North-West frontier. This paper also tells about the quality of Ranjit Singh’s army and his coutries. This is also tells Ranjit Singh’s relation with Britsher, Maratha, Afghans and other cities.